(3Lfi GdLfGSs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf CUWai gPG CdaJg ai CbSGe GdLfGS GdJi ESJNQLJgG hMUQJgG hSejJg Lfi GdLfGS hHGddg CYhP QH GdfGS Cbhd CUhd CfhGY GdLfGS NeSI YTQ fhYkG s
(3BNQgG (B:s
(3hce dg UM eYJd hdGM dg fhQ hfGQ ef GdJhajb hGdgee HOQ GdJeGe GdPi CMjG HWdYGg djd GdJeGe eVGa Gdjhe HGdNOe Ke Pdc BNQg hGdMeO ddg hMOg hMSHfG Gddg hfYe Gdhcjd s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B607s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(336) s
Keywords: (3GddZIs